Role of Diet in the Management of Carcinoid Syndrome: Clinical Recommendations for Nutrition in Patients with Neuroendocrine Tumors. (2nd January 2022) - Artale, Salvatore; Barzaghi, Sabrina; Grillo, Nunziata; Maggi, Claudia; Lepori, Stefano; Butti, Chiara; Bovio, Antonella; Barbarini, Lucia; Colombo, Andrea; Zanlorenzi, Laura; Castiglioni, Elena; Trojani, Alessandra
Abstract: Nutrition and metabolism are altered in patients with gastroenteropancreatic neuroendocrine tumors, which is related to excessive production of gastrointestinal hormones, peptides, and amines that can cause maldigestion, diarrhea, steatorrhea, and altered gastrointestinal motility. Patients with carcinoid syndrome are at risk of malnutrition due to tryptophan depletion, reduced intake of food, and loss of appetite because of diarrhea and/or flushing. To date, there is limited information on the nutritional issues faced by patients with neuroendocrine tumors, and on what specific recommendations should be made to patients concerning nutrition at various stages of the disease process. Dietary planning should therefore be an integral part of multidisciplinary management for patients with neuroendocrine tumors. Herein, we review current guidance for nutrition in patients with neuroendocrine tumors, focusing on intake of amines and foods to avoid, as well as concurrent medications. We also propose a new and practical food pyramid based on the principles of Mediterranean diet 4.0 that can be easily adapted according to the unmet needs of patients with neuroendocrine tumors at all stages of disease. The overarching goal of the present review is to create greater awareness of nutritional care and considerations that should be given to patients with neuroendocrine tumors.